2005
DOI: 10.1038/emm.2005.7
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial injury occurs earlier than myocardial inflammation in acute experimental viral myocarditis

Abstract: Abbreviations: CK-MB, creatine kinase MB isoform; CVB3, coxsackievirus group B3; CVB3-H3, myocarditic H3 strain of CVB3; CVB3-10A1, less myocarditic variant of CVB3-H3; PFU, plaque forming unit; m.o.i, multiplicity of infection; cTnT, cardiac isoforms of troponin T; EMB, endomyocardial biopsy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The absence of increased serum cTnI concentrations and the lack of histologic evidence of cardiomyocyte degeneration differentiate the condition described here from the findings in models of myocarditis, in which increases in serum cTn are associated with cardiomyocyte damage (Bachmaier et al 1995;Lim et al 2005;Smith et al 1997). As reported here, normal serum concentrations of cTnI in monkeys with myocardial mononuclear cell infiltrates imply that cardiomyocyte damage, not cellular infiltration, is responsible for the serum cTnI increases seen in animal models of myocarditis.…”
Section: Discussionsupporting
confidence: 58%
“…The absence of increased serum cTnI concentrations and the lack of histologic evidence of cardiomyocyte degeneration differentiate the condition described here from the findings in models of myocarditis, in which increases in serum cTn are associated with cardiomyocyte damage (Bachmaier et al 1995;Lim et al 2005;Smith et al 1997). As reported here, normal serum concentrations of cTnI in monkeys with myocardial mononuclear cell infiltrates imply that cardiomyocyte damage, not cellular infiltration, is responsible for the serum cTnI increases seen in animal models of myocarditis.…”
Section: Discussionsupporting
confidence: 58%
“…35 It was reported that the serum cardiac troponin concentration was an earlier marker of myocardial injury after virus infection than was the histologic finding of inflammation. 25 The increase of serum cTnI and reduction or loss of cTnI expression in tissue are roughly related to disease severity, probably reflecting the extent of inflammatory and degenerative changes of the myocardium. In humans, maintenance of high serum concentrations of cTnI was considered an indication of a poor prognosis in advanced heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, because each pony had a normal prechallenge cTnI, and the CON ponies did not have variations in cTnI over the same duration of time, the transient increases suggested that they were associated with viral challenge. Definitive proof of cause and effect would have required endomyocardial biopsies, but cardiac troponins have been used to follow both clinical and experimentally induced viral myocarditis in people and laboratory animals 12,17,18 …”
Section: Discussionmentioning
confidence: 99%
“…Cardiac troponin I (cTnI) concentrations are increased in a number of human cardiac diseases, including viral myocarditis 12,16,17 . Both cTnI and cardiac troponin T (cTnT) have been used to monitor viral myocarditis in people, 12,17 and cTnT has been shown to correlate well with viral infection in the heart, and to precede the development of histologically confirmed inflammation in a mouse model of myocarditis 18 . In this experimental model, cTnT concentrations increased by day 3 after infection, persisted at day 7, and had returned to normal by day 14.…”
mentioning
confidence: 99%